The Antibacterial Effects of Resin-Based Dental Sealants: A Systematic Review of In Vitro Studies - Saad Saeed AlShahrani (Materials, 2021)
This review aimed to assess the antimicrobial effects of different antibacterial agents/compounds incorporated in resin-based dental sealants. Four databases (PubMed, MEDLINE, Web of Science and Scopus) were searched. From the 8052 records retrieved, 275 records were considered eligible for full-text screening. Nineteen studies met the inclusion criteria. Data extraction and quality assessment was performed by two independent reviewers. Six of the nineteen included studies were judged to have low risk of bias, and the rest had medium risk of bias. Compounds and particles such as zinc, tin, Selenium, chitosan, chlorhexidine, fluoride and methyl methacrylate were found to be effective in reducing the colony-forming unit counts, producing inhibition zones, reducing the optical density, reducing the metabolic activities, reducing the lactic acid and polysaccharide production and neutralizing the pH when they are added to the resin-based dental sealants. In addition, some studies showed that the antibacterial effect was not significantly different after 2 weeks, 2 months and 6 months aging in distilled water or phosphate-buffered saline. In conclusion, studies have confirmed the effectiveness of adding antibacterial agents/compounds to dental sealants. However, we should consider that these results are based on laboratory studies with a high degree of heterogeneity.